Enterprising characteristics in nursing students - Páramo-Gutierrez, Guadalupe Lizbeth (Universidad de Sonora, 2019)
Introduction: Enterprising is the individual behavior that tends to the challenge, to create new conditions and improve existing realities, aiming at the pursuit of an independent career in the future. Objective: To know the enterprising characteristics of nursing students. Methodology: Descriptive transversal study, involving 188 nursing students from a Higher Education Institution in Guanajuato, Mexico, available at the time of the data collection, who responded to the Enterprising Attitude Scale, for the data analysis descriptive statistics was obtained, we had the informed consent from the participants. Results: 77.1% were women, with an age range between 18 to 26 years old, 50.5% reported having work experience. In relation to enterprising characteristics, 36.2% refer to aim for excellence in everything they do, 64.5% consider that everything is possible if they believe they can do it, 68.6% always try to learn from their own mistakes, 37.8% are able to imagine how things can be done to work. Conclusion: The results show the enterprising characteristics of the participants in which stand out to have confidence in their projects, excellence in everything they do, among others. For this reason, this study gives indications of the emphasis on the formation that nursing professionals oriented to enterprising should have, to favor an autonomous practice.